EMI filter design for single‐phase grid‐connected inverter with noise source impedance consideration. Issue 17 (19th January 2021) - Liu, Yitao; Ye, Xin; Peng, Jianchun
Abstract : It is well known that noise source impedance plays a significant role in designing conducted electromagnetic interference (EMI) filters. However, the noise source impedance in a switched‐mode power supply is not easy to extract. In this study, the noise source impedance in a single‐phase inverter is extracted under operating conditions based on a two‐probe approach. First, the noise source modelling and analysis are implemented for the inverter system to illustrate the importance of impedance. Furthermore, the proposed two‐probe method is introduced and then validated by several passive components. Proper and straightforward premeasurement calibrations are needed to eliminate the influence of the probes and cables. The approach can accurately extract the common‐mode and differential‐mode noise source impedances with different configurations according to the characteristics of their propagation paths. Compared with a traditional EMI filter design, the experimental results show that the one designed by the proposed approach can effectively attenuate the conducted EMI noises to meet the requirements with more appropriate and optimised parameters.